Public policies and tax evasion: evidence from SAARC countries. Issue 11 (November 2020) - Islam, Azharul; Rashid, Md. Harun Ur; Hossain, Syed Zabid; Hashmi, Rubayyat
Abstract: In compliance with the socioeconomic theory, the study has strived to investigate the impact of economic and non-economic public policies on tax evasion using panel data of 7 SAARC countries covering the period from 1998 to 2015. The study has applied the ordinary least square with fixed effect and random effect models to analyze the data assembled. The result of the study implies that the higher the degree of economic freedoms, the lower the tax evasion. More specifically, the government policies about property rights, monetary freedom, fiscal freedom and investment freedom have a negative influence on taxpayers' choices of tax evasion while financial freedom result shows a positive effect on tax evasion. Additionally, there is a negative impact of public sector governance and religiosity on tax evasion, which implies the higher the public sector governance and the higher the religious faith amid the people, the lower the degree of tax evasion. The findings of the study are supposed to offer the governments, tax authorities, and research scholars the valuable insights into public policies for reducing the tax evasion to a significant extent. Abstract : Tax evasion; Public policies; Economic freedom; Good governance; Religiosity; SAARC Countries; Economics; Public finance; Accounting; Macroeconomics; Business policy